Ocular Manifestation of the Pediatric Age Group in Almarj - Marwa Amish; Yasmena Abdulhadi (AlQalam Journal of Medical and Applied Sciences, 2024)
Children are disproportionately affected by visual disorders like refractive errors, amblyopia, and strabismus. Early intervention and vision screening are crucial. The study aims to investigate the ocular manifestation among children of the age group 4–15 years. A cross-sectional study conducted at Marj Teaching Hospital in 2024 examined 100 children with ophthalmological conditions. The examinations included slit lamp examinations, visual acuity assessments, spherical refractive error measurements, and dilated retinal exams. The study examined children aged 4-15 years old, with 59% being male and 43% female. Diagnosis revealed a range of ocular conditions, with astigmatism being the most common at 48%. There were significant differences in visual acuity between males and females (p<0.001), particularly in left eye visual acuity without glasses. There was no significant difference in visual acuity between age groups when wearing or not wearing glasses. However, there was a trend towards better right-eye visual acuity for children aged 4-10 years compared to those aged 11-15 years (p<0.001). Refractive errors with a higher prevalence of simple astigmatism in females compared to males. High hypermetropia was only present in females, suggesting some differences in refractive errors between males and females, particularly hypermetropia. The study emphasizes the significance of regular eye examinations for detecting and addressing visual impairments, and calls for further research into factors contributing to these conditions, particularly male-female differences, to improve eye health and quality of life. we highly advocate assessing the visual acuity of preschool children in order to prevent amblyopia. يتأثر الأطفال بشكل غير متناسب بالاضطرابات البصرية مثل الأخطاء الانكسارية والحول، بالإضافة الى الصدمات العينية. التدخل المبكر وفحص الرؤية أمر بالغ الأهمية. تهدف الدراسة إلى تقصي المظاهر العينية لدى الأطفال في الفئة العمرية 4-15 سنة. أجريت دراسة مقطعية في مستشفى المرج التعليمي عام 2024 لفحص 100 طفل يعانون من أمراض العيون. وشملت الفحوصات فحوصات المصباح الشقي، وتقييمات حدة البصر، وقياسات الخطأ الانكساري الكروي، وفحوصات الشبكية المتوسعة. فحصت الدراسة الأطفال الذين تتراوح أعمارهم بين 4 و15 سنة، 59% منهم ذكور و43% إناث. كشف التشخيص عن مجموعة من الحالات العينية، وكان اللانقطية هو الأكثر شيوعًا بنسبة 48٪. وكانت هناك فروق ذات دلالة إحصائية في حدة البصر بين الذكور والإناث[P<0.001]، وخاصة في حدة البصر بالعين اليسرى بدون نظارات. ولم يكن هناك اختلاف كبير في حدة البصر بين الفئات العمرية عند ارتداء النظارات أو عدم ارتدائها. ومع ذلك، كان هناك اتجاه نحو تحسين حدة البصر بالعين اليمنى لدى الأطفال الذين تتراوح أعمارهم بين 4 و10 سنوات مقارنة بمن تتراوح أعمارهم بين 11 و15 عامًا [P<0.001]. الأخطاء الانكسارية مع ارتفاع معدل انتشار اللانقطية البسيط لدى الإناث مقارنة بالذكور. كان طول النظر العالي موجودًا فقط عند الإناث، مما يشير إلى بعض الاختلافات في الأخطاء الانكسارية بين الذكور والإناث، وخاصة طول النظر. تؤكد الدراسة على أهمية فحوصات العين المنتظمة للكشف عن الإعاقة البصرية ومعالجتها، وتدعو إلى إجراء مزيد من الأبحاث حول العوامل التي تساهم في هذه الحالات، وخاصة الاختلافات بين الذكور والإناث، لتحسين صحة العين ونوعية الحياة. نحن نؤيد بشدة تقييم حدة البصر لدى الاطفال من أجل الوقاية من كسل العين.